ANALISIS TATA LETAK GUDANG PRODUK JADI KAIN TUBULAR DENGAN METODE CLASS-BASED STORAGE DI PT. ABC - Rifqi Miftahussidik; Eka Ludiya (JURNAL ILMIAH EDUNOMIKA, 2024)
PT. ABC is a textile manufacturing company that provides knitting, dyeing, finishing and printing processes for all high quality fabrics. Companies face warehouse capacity problems, at certain times experiencing capacity shortages. If the warehouse does not have sufficient capacity, products will be stored in the line aisles, thereby impacting warehouse operations. The purpose of this research is to determine the planning, implementation, evaluation of the warehouse layout for finished tubular fabric products and to determine improvement efforts using the class-based storage method. This research method uses a qualitative approach using the term social situation. The data sources for this research are observation, interviews with key company informants and documentation in the form of details of warehouse area and warehouse stock data. Test validity and reliability using triangulation of sources, techniques and time. The results of this research, with improvements made using the class-based storage method, can minimize the material movement distance by 57.98 meters and increase the capacity to 181 pallets with a total capacity of 108,600 kg. From the research results it can be concluded that the application of the class-based storage method can overcome the problem in the warehouse of finished products of tubular fabric